Integrated Computing Technology c - Hruschka, Estevam Rafael; Watada, Junzo; Carmo Nicoletti, Maria; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the First International Conference on Integrated Computing Technology, INTECH 2011, held in Sao Carlos, Brazil, in May/ June 2011. The 14 revised full papers presented were carefully reviewed and selected from 103 submissions. The conference fosters discussions in integrating models, framework, designs, content,networks and the knowledge through more robust and high quality research.
Keywords: Computer science; Computer Communication Networks; Computer software; Database management; Information storage and retrieval systems; Information systems; Computer Science; Algorithm Analysis and Problem Complexity; Information Systems Applications (incl.Internet).; Database Management; Computation by Abstract Devices; Information Storage and Retrieval; Computer Communication Networks